Tela’ah Takhrij Hadis Cinta Tanah - Supriyono; Damanhuri (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
With a sense of love for the country that every citizen has, it will make the country in a better condition. Every citizen is obliged to have a feeling of love for the homeland because the homeland is where they stand culturally and historically. Love for one's country is not enough just to say it in words, but must be proven or realized through real action in deeds in an effort to improve the nation's order. Love for the homeland is love with full affection and devotion to the country and taking part in maintaining its preservation and being willing to make sacrifices for the integrity of the nation and state. One sign that someone has an attitude of love for their country is that they want to appreciate works of art and national culture. By being marked as someone who has an attitude of patience in the process, and has wisdom in life, this can foster a sense of love for one's own nation and country, with such characteristics and attitudes a high sense of nationalism will also grow and a feeling of love for one's country towards the nation can be justified. his country.